2018
DOI: 10.1111/infa.12229
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Infant Gesture and Joint Attention as Related Constructs and as Predictors of Later Language

Abstract: In infancy, use of gesture and the ability to engage in joint attention with others both predict later language development. Conceptually, gesture and joint attention abilities may reflect a similar underlying social communicative skill. However, these abilities are often studied separately. Despite the fact that gesture is often used in episodes of joint attention, little is known about the degree to which measures of gesture use and joint attention ability are associated with one another or how they similarl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 51 publications
2
42
0
2
Order By: Relevance
“…However, given the specificity of the type of pointing, it is also possible that infants' declarative pointing might moderate rather than mediate a relation between parent declarative pointing and infant language skills. There is evidence that infants' production of points is related to their understanding of the same gesture (Behne, Liszkowski, Carpenter, & Tomasello, 2012;Liszkowski & Tomasello, 2011;Woodward & Guajardo, 2002), and the same seems to be true specifically for declarative points (Salo et al, 2018). Thus, perhaps infants who are already producing declarative points, and thus displaying an early behavioral marker of symbolic communication and intention understanding, are better able to understand the significance of others' declarative points and use those observed declarative points to support them in learning new words.…”
Section: The Current Studymentioning
confidence: 92%
See 1 more Smart Citation
“…However, given the specificity of the type of pointing, it is also possible that infants' declarative pointing might moderate rather than mediate a relation between parent declarative pointing and infant language skills. There is evidence that infants' production of points is related to their understanding of the same gesture (Behne, Liszkowski, Carpenter, & Tomasello, 2012;Liszkowski & Tomasello, 2011;Woodward & Guajardo, 2002), and the same seems to be true specifically for declarative points (Salo et al, 2018). Thus, perhaps infants who are already producing declarative points, and thus displaying an early behavioral marker of symbolic communication and intention understanding, are better able to understand the significance of others' declarative points and use those observed declarative points to support them in learning new words.…”
Section: The Current Studymentioning
confidence: 92%
“…reliably produce declarative points at this age (Knudsen & Liszkowski, 2013;Liszkowski et al, 2004Liszkowski et al, , 2006Liszkowski et al, , 2008. However, other studies have shown significant variation in infants' production of both imperative and declarative points around 12 months (Brooks & Meltzoff, 2008;Lüke et al, 2017;Mundy et al, 2007;Salo, Rowe, & Reeb-Sutherland, 2018). It is still unclear what factors predict these individual differences.…”
Section: Infant Pointingmentioning
confidence: 94%
“…The ability to imitate the goals of actions in the second year of life predicts language production skills at 3 years (Charman et al, 2000) and can even predict whether an infant exhibits later language delays (Zambrana, Ystrom, Schjølberg, & Pons, 2013). Engaging in joint attention, which involves sharing attention with a partner to a third entity, such as when an infant is attending simultaneously to both a parent and a toy (Seibert, Hogan, & Mundy, 1982;Tomasello & Farrar, 1986), involves much of the behaviors used to measure infants' action understanding listed above and has been implicated as a manifestation of infants' intention understanding (Salo, Rowe, & Reeb-Sutherland, 2018). In line with this interpretation, there is a bounty of evidence linking infants' ability to initiate and respond to bids for joint attention with concurrent and later language abilities (Bates, Benigni, Bretherton, Camaioni, & Volterra, 1979;Camaioni, Castelli, Longobardi, & Volterra, 1991;Desrochers, Morissette, & Ricard, 1995;Markus, Mundy, Morales, Delgado, & Yale, 2000;Morales et al, 2000;Morales, Mundy, & Rojas, 1998;Mundy & Gomes, 1998).…”
Section: Ac Tion Under S Tanding and Communic Ationmentioning
confidence: 99%
“…First, infants use so called whole-hand points, in which the arm and the hand are extended toward a referent, followed by index-finger points, in which the arm and the index finger are clearly extended toward a referent (Lock et al, 1990;Liszkowski and Tomasello, 2011;Lüke et al, 2017b). Based on the large number of studies it is undisputable that the production of pointing gestures is a strong predictor for later language skills (for a meta-analysis see Colonnesi et al, 2010 (for recent research see Murillo and Belinchón, 2012;Beuker et al, 2013;Kuhn et al, 2014;Lüke et al, 2017aLüke et al, , 2019Salo et al, 2018). Yet, there is some debate about the specific aspect of pointing gestures responsible for this predictive value.…”
Section: Introductionmentioning
confidence: 99%
“…Number of pointing gestures (Beuker et al, 2013;Kuhn et al, 2014;Lüke et al, 2017b); 3. Intention of pointing gestures (Colonnesi et al, 2010;Lüke et al, 2017a;Salo et al, 2018); 4. Hand shape of pointing gestures (Liszkowski and Tomasello, 2011;Murillo and Belinchón, 2012;Lüke et al, 2017aLüke et al, ,b, 2019; 5.…”
Section: Introductionmentioning
confidence: 99%